REKONSTRUKSI KEBIJAKAN PENANGGULANGAN KEJAHATAN BERDASARKAN KEADILAN RESTORATIF DALAM KERANGKA PERADILAN PIDANA YANG BERKEPASTIAN HUKUM - Nugroho, Sofyan (Jurnal Ilmu Kepolisian, 2023)
Restorative justice-based criminal policies within the framework of criminal justice which has legal certainty carried out by Polri (Indonesian National Police) are implemented through Penal and non-Penal policies. Penal policies are carried out by investigators as the function of law enforcement, and non-Penal policies are carried out by bhabinkamtibmas (a police sergeant assigned to take care problems related to laws in a village or sub-district) as the function of pre-emptive efforts and patrol unit as the function of preventive efforts.Overcoming crimes based on restorative justice intent to solve problems of society in such a way. The problems can be resolved using the principle of restorative justice, that is, the sense of justice for each party involved in the problems can be realized. Such overcoming involves victims, perpetrators, victims' families and the community as well as the relevant parties in order to reach a fair agreement and settlement.The research focuses on restorative justice in Polri. Meanwhile, the problem questions of the research are: (1) How is the construction (ius constitutum) of crime prevention policies based on restorative justice within the criminal justice framework that has legal certainty? (2) How is the implementation (ius operatum) of crime prevention policies based on restorative justice within the criminal justice framework that has legal certainty? And (3) How is the reconstruction (ius constituendum) of crime prevention policies based on restorative justice within the framework of criminal justice with legal certainty?The research employs the normative juridical approach. The research employs secondary and primary data. Secondary data is obtained by conducting library research and documentary studies, and primary data is obtained by conducting interview studies. Data is then analysed using the mix method (quantitative and qualitative).The results of the research reveal that (1) the construction of crime prevention policies is seen from a philosophical aspect based on Pancasila values and the principles of restorative justice; from a juridical aspect by taking into account legal norms originating from abroad, customary law, Islamic law, and national law, all of which are rooted in Pancasila values; from a sociological aspect that it needs the active participation from the community in supporting the crime prevention based on restorative justice, (2) the implementation of crime prevention policies based on restorative justice using Penal and Non-Penal carried out by the investigative function, bhabinkamtibmas and patrol units, to parse and resolve existing problems in society, and (3) the reconstruction of crime prevention through substance aspects in the forms of renewing Criminal Procedure Code and police regulations, structural aspects of compiling restorative justice mechanisms and increasing personnel competence, cultural aspects in the form of increasing community participation to be aware of laws and support restorative justice programs.